Institutionalized Democracy and the Shadow Economy in the Short- and Long-run: Empirical Analysis from Uganda - Esaku, Stephen (Humanities and Social Sciences Communications, 2022)
This paper investigates the relationship between institutionalized democracy and the shadow economy in both the long- and short-run. Using time series data from Uganda that cover the period from 1991 to 2015, this paper applies autoregressive distributed lag method to investigate this relationship. How democracy affects the shadow economy in less developed countries like Uganda is not well understood. This paper aims to fill the above knowledge gap. The findings show that the shadow economy and institutionalized democracy are negatively correlated in both the short- and long-run. This implies that improvement in institutionalized democracy significantly hinders the rise of shadow activities. This indicates that institutions regulate the conduct of economic agents and determine how entrepreneurs engage in economic activities. Moreover, institutions are crucial in resource allocation which in turn leads to welfare improvement. Improvement in welfare of citizens reduces their incentive to engage in informal sector activities since the formal sector provides the necessary support needed to operate legally. These findings are robust to alternative econometric methods. Two practical implications of these findings stand out. First, these findings indicate that reforming the governance system to facilitate efficient resource allocation could be one way of addressing widespread informality in developing economies. Second, these results also indicate that minimizing informality in the economy should gradually move away from emphasis on tackling proximate causes of informality to democratic reforms that change the authority patterns. In this case institutionalized democracy is another important channel of mitigating the rise of the shadow economy.